The Influence of High-Performance Work Systems (HPWS) And Emotional Intelligence on Adaptive Performance: The Mediating Role of Work Engagement at The Directorate General of Public Health (Ditjen Kesmas) - Yulyani, Deni; Martdianty, Fanny (Jurnal Locus Penelitian dan Pengabdian, 2025)
Conditions of uncertainty always occur in an organization due to changes, so adaptive performance is needed to face all these changes. Linked to previous research which examined the influence of high-performance work systems which can have an influence on organizational outcomes, one of which is adaptive performance. Apart from that, in dealing with change, emotional intelligence is needed in order to be able to think appropriately about one's emotions so that one can adapt to changes. Therefore, the aim of this research is to determine the influence of high-performance work systems and emotional intelligence on adaptive performance. Then in relation to the relationship between the three, work involvement plays a mediating role which is expected to strengthen or weaken the relationship between the three. The research sample of 239 people was then processed using Structural Equation Modelling (SEM) techniques and Lisrel version 8.80 as the application used in processing the data. The results show that there is a significant positive direct influence between HPWS and adaptive performance and emotional intelligence and adaptive performance. In addition, work engagement can partially mediate the influence of HPWS and emotional intelligence on adaptive performance.